The Management of Synchronous Bilateral Wilms Tumor: A Report from the National Wilms Tumor Study Group - Hamilton, Thomas E. (2011)
OBJECTIVE: To provide guidelines for future trials, we reviewed the outcomes of children with synchronous bilateral Wilms tumors (BWT) treated on National Wilms Tumor Study-4 (NWTS-4). METHODS: NWTS-4 enrolled 3,335 patients (pts) including 188 pts with BWT (5.6%). Treatment and outcome data were collected. RESULTS: Among 188 BWT pts registered with NWTS-4, 195 kidneys in 123 patients had initial open biopsy, 44 kidneys in 31 pts had needle biopsies. Although pre-resection chemotherapy was recommended, 87 kidneys in 83 pts were managed with primary resection: Complete nephrectomy 48 in 48 pts, 31 partial/wedge nephrectomies in 27 pts, enucleations 8 in 8 pts. No initial surgery was performed in 45 kidneys in 43 pts, 5 kidneys in 3 pts not coded. Anaplasia was diagnosed after completion of the initial course of chemotherapy in 14 pts (initial surgical procedure: 9 open biopsies, 4 needle biopsies, 1 partial nephrectomy). The average number of days from the start of chemotherapy to diagnosis of anaplasia was 390 (range 44–1,925 days). Relapse or progression of disease occurred in 54 children. End stage renal failure occurred in 23 children, 6 of whom had bilateral nephrectomies. The 8 year event free survival (EFS) for BWT with favorable histology was 74%, and overall survival (OS) was 89%; while the EFS for BWT with unfavorable histology was 40%, OS was 45%. CONCLUSION: The current analysis of patients with BWT treated on NWTS-4 shows that preservation of renal parenchyma is possible in many pts following initial preoperative chemotherapy. The incidence of end-stage renal disease remains significantly higher in children with BWT. Future studies are warranted to address the need for earlier biopsy in non-responsive tumors and earlier definitive surgery to recognize unfavorable histology in these high risk patients.